Structuring care: checklist for asthma and COPD consultation (Portuguese Journal of Family Medicine and General Practice, 2025)
Consultation constitutes the central activity of family medicine, which is essential for the acquisition of the competencies outlined in the profile of the family doctor during training so that these can be efficiently applied in daily practice. Chronic respiratory diseases, particularly asthma and COPD, benefit from a structured and schematized approach for better disease control. We present two checklists, based on the most recent guidelines, as versatile tools for managing patients with asthma or COPD. We propose using these checklists by any professional involved in the care of chronic respiratory diseases. They can be used to enhance daily clinical practice and throughout training during family medicine residency. Depending on their intended purpose, they can be useful tools for clinical skills training and self-and peer assessment. We hope that this will contribute to the management of respiratory disease in primary care.
Keywords: Asthma; Chronic obstructive lung disease; Checklist; Teaching; Medical education